The lights and shadows of the open access regulatory framework at the General Government Administration in Spain - Clabo Clemente, Néstor (Revista General de Información y Documentación, 2015)
This paper aims at reviewing the open access regulatory frame work at the General Government Administration in Spain to observe how it affects its performance. To achieve such goals this study first compiles and analyses a whole range of rules, provisions, statements and existing calls in Spain and the European Union on comparative bases. The conclusion is the absence of specific and general European and national legal frame works affecting the open access. The main information collected appear partially ortangentially in programs and calls for funding of research projects, communications, and reuse and open data regulation. Even the Law 14/2011 of Science, Technology and Innovation does not provide a sufficiently clear mandate, and the new amendment to the Copyright Act does not contribute to clarify the situation neither. The focus is usually on the repositories, indicating a preference for the green road to ensure open access to journal content.
Keywords: Europea Union; General Government Administration; Green Road. Open Access; Regulation; Science Policy; Spain; Reuse; Repositories.